Growth Responses and Nitrogen Uptake by Saltgrass (Distichlis spicata L.), a Halophytic Plant Species, under Salt Stress, Using the 15N Technique. (11th April 2012) - Pessarakli, Mohammad; Harivandi, M. A.; Kopec, David M.; Ray, Dennis T.
Abstract : Various saltgrass clones were studied hydroponically, using Hoagland solution, in a greenhouse to evaluate their DM weights and nitrogen uptake under control and salt stress conditions. Treatments included control (no added salt) and plants grown under NaCl salinity. Twelve clones were grown with 4 replications of each treatment in a RCB design trial. Ammonium sulfate, 5.3% 15 N was used to enrich the plants by adding 5 mg 15 N as 22.931 mg ( 15 NH4 )2 SO4, per liter of the culture solution per day. Plant shoots were harvested weekly, oven-dried at 65°C, and DM weights were recorded. At the last harvest, plant roots were also harvested, oven-dried at 65°C, and DM weights were determined. Harvested plant materials were analyzed for total-N and 15 N contents. The results showed non-significant differences in shoot DM weights and total-N and 15 N concentrations and contents in salinized plants compared with the controls. Total-N and 15 N concentrations of the roots were higher than that of the shoots under either control or saline condition. Overall, due to the high degree of salt tolerance of saltgrass, the results showed generally no difference in nitrogen uptake by most of the clones under salt stress compared with the control plants.